Interface treatment and performance study on fiber tube reinforced polyvinylidene fluoride hollow fiber membranes. Issue 7 (2nd July 2020) - Liu, Liyan; Shen, Hongdou; Li, Ting; Han, Yongliang
Abstract: The fiber tube reinforced hollow fiber membranes are widely used in membrane bioreactor (MBR) due to their excellent mechanical and filtered properties. However, the poor adhesive power between fiber tubes and membranes restricted their service life in practice applications. Herein, we supply a facile and feasible surface coating modification methods for optimizing the interfacial bonding ability. The outer surfaces of the braided and knitted tubes were modified with silane coupling agent KH570 and acrylate adhesive before the fiber tube reinforced hollow fiber membranes were fabricated. The effects of different modifiers dosages on the morphology, tensile strength, bursting strength, pure water flux, porosity and mean pore size of the braided and knitted tubes reinforced hollow fiber membranes were evaluated respectively. Moreover, the effects of different modifiers on the fabric tubes with different structure were analysed. The results showed that the optimum dosage of the two modifiers was 3 g/5m. It is revealed that the minute quantities of modifiers applied to the tubes could improve not only the interfacial combination of the reinforced membrane, but also their strength and penetration performance.